WHEN THE KERALA MODEL OF DEVELOPMENT IS HISTORICISED: A CHRONOLOGICAL PERSPECTIVE - P.K. MICHAEL THARAKAN (CSESWP19, 2008)
This study indicates that the evolution of `Kerala Model of development' was one sided. In its two momentous phases; one of commercialization of agriculture on the basis of which Socio-Religious Reform Movements emerged and the other of politicization of people's demands which crystallized in Land Reforms; it provided numerous options for social and economic advancement to the middle level caste, communities and also to the `middle classes'. The relatively underprivileged also benefited and in their struggles for rights as well as social benefits, members of middle level castes, communities and classes participated. Such traditions are still maintained by alert and democrative mass and class movements who act as defenders of public welfare. Yet it is proposed in this study that the development experience in Kerala has resulted ultimately in weakening the material basis of public action. On limited evidence it is pointed out that the poor in Kerala society are likely to be trapped into a situation of lesser assets and relatively lessincomes in the foreseeable future; thereby further increasing not only economic but also social cleavages. Such developments are likely to adversely affect the public-mindedness of even the organized sections of middle level castes and classes. It need not necessarily result in the total unmaking of the democratic and progressive traditions of Kerala's public sphere, but preserving those traditions is likely to face great pressure. It also raises doubts about exclusively entrusting the development approach so far followed, to solve problems of poverty and marginalization